Hydrogen-assisted failure in Inconel 718 fabricated by laser powder bed fusion: The role of solidification substructure in the embrittlement. (15th January 2022) - Lee, Dong-Hyun; Zhao, Yakai; Lee, Soo Yeol; Ponge, Dirk; Jägle, Eric A.
Abstract: The influence of hydrogen on the mechanical behavior of Inconel 718 fabricated by laser powder-bed-fusion was investigated through a series of tensile experiments. Samples subjected to two different post-fabrication heat treatments, viz. direct aging (DA) and homogenization plus aging (HA), were tested. Detailed microstructural characterization showed that a solidification substructure including a high density of dislocations and precipitates prevails in the DA sample while the HA sample is free from such a substructure. The DA sample exhibited a comparatively higher strength, but a lower resistance to hydrogen embrittlement. By recourse to a statistical analysis of the hydrogen-assisted cracks, the severe hydrogen embrittlement of the DA sample was proven to be due to the significant portion of hydrogen-assisted intergranular cracks that occurred without the aid of slip localization. These results are discussed in terms of the changes in microstructure upon heat treatments, and their influences on the hydrogen trapping sites. Graphical abstract: Image, graphical abstract